"Muslim Christology": The Islamization of the Gospels in the Muslim Biblical Scholarship - Dadi Darmadi (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
This paper tries to discuss the biblical texts and their interpretation in the Islamic tradition. It will essentially explore the specific relations be-tween the Qur’an, and the Bible, and how some Muslim scholars interpret the biblical texts in accordance with the Islamic doctrines. Even though the term “Islamization” of the Gospels has not been widely used in the Muslim scholarship, many Western scholars of Islam have referred to this as one of the major features of the Qur’anic discussion on Jesus and Christian tradition.